Pharmacological Treatment for Social Cognition: Current Evidence - Riccardi, Cecilia (Int J Mol Sci, 2021)
Cognitive impairment is currently considered a core feature of schizophrenia (SZ) and is gaining attention as a fundamental therapeutic target. Standard treatment for SZ involves the use of antipsychotics that are successfully used to control positive symptoms and disorganized behaviour. However, it is still unclear whether they are effective on social cognition (SC) impairment. Furthermore, different medications are currently being studied to improve SC in patients with SZ. A literature search on this topic was conducted using the PubMed database. All kinds of publications (i.e., reviews, original contributions and case reports) written in English and published in the last 15 years were included. The aim of our literature review is to draw a picture of the current state of the pharmacological treatment of SC impairment in SZ.